Social Support and Self-Esteem as Predictors of Psychological Distress among Students with Learning Disabilities in Accra, Ghana (Global Journal of Human-Social Science, 2021)
Using a survey research design this study examined the extent to which social support and selfesteem predict psychological distress among students with learning disabilities at Multi Kids Inclusive Academy in Accra Ghana The Simple Random Sampling technique was used to select 94 students Survey questionnaires containing the Child and Adolescent Social Support Scale Malecki Demaray 2002 Depression Anxiety and Stress Scale Lovibond Lovibond 1995 and Adapted Rosenberg Self Esteem Scale Dagnan Sandhu 1999 were used to collected data Descriptive statistics Reliability and Normality tests Simple Linear Regression Analysis and the Pearson Product Moment Correlation Coefficient test within the Statistical Package for Social Sciences SPSS version 23 application software were used to analyze data Results indicated that Social Support from Teachers 202 p 033 and Social Support from Classmates 548 p 000 predicts psychological distress Social Support from Parents Dimension subscale - 024 p 810 did not predict psychological distress In addition a significant negative relationship was found between self- concept and psychological distress Also differences in gender - 238 p 033 and age 266 p 017 predicts psychological distress